Focused Review: Agmatine in Fermented Foods - Galgano, Fernanda; Caruso, Marisa; Condelli, Nicola; Favati, Fabio (Frontiers in Microbiology, 2012)
Polyamines (PAs) are ubiquitous substances considered to be bioregulators of numerous cell functions; they take part in cell growth, division, and differentiation. These biogenic amines are also involved in tissue repair and in intracellular signaling; in fact, because of their polycationic character, they interact to a large extent with membrane phospholipids and may play an important role in the regulation of membrane-linked enzymes. The intracellular polyamine content derives from the simultaneous regulation of the synthesis, catabolism, uptake, and elimination of the polyamines; furthermore, PAs are present in all cell types at different concentrations, but the highest levels are found in rapid-turnover tissues. In addition to spermidine, spermine, and putrescine, also agmatine (AGM), deriving from arginine and identified in mammals in the 1990s, is a polyamine and several studies have reported its potentially positive role in the production of secretagogues, and in neuronal, vascular, metabolic, and therapeutic functions. Because of the low arginine decarboxylase (ADC) activity in mammalians, the amounts of AGM found in their tissues can be only minimally ascribed to an endogenous de novo synthesis by ADC, while a substantial quantity of AGM may be of dietary origin. Several food products contain only small amounts of polyamines, while higher concentrations can be found in fermented foods. PAs could also be considered as indicators of freshness in fish and meat products; as these moieties are produced during food storage, it would seem to confirm the main role of microorganisms in their synthesis. In particular, high levels of AGM are present in alcoholic beverages, such as wine, beer, sake, which would seem to confirm the role of yeasts in AGM production. Although many biological functions have been attributed to polyamines, high levels of these compounds in foodstuffs can have toxicological effects; however, no safe level for the intake of polyamines in a diet has yet been established. In this paper the presence of AGM in different foodstuffs is discussed, also taking into account the various factors affecting its presence and concentration.